Validade de indicadores de atividade física e sedentarismo obtidos por inquérito telefônico - MONTEIRO, Carlos Augusto (2013)
OBJECTIVE: To assess the reliability and validity of indicators of physical activity and sedentariness obtained by means of a telephone-based surveillance system. METHODS: Reliability and validity studies were carried out in two random subsamples (n=110 and n=111, respectively) obtained from the total sample (N=2,024) of adults (≥18 years) studied by the system in the municipality of São Paulo in 2005. Studied indicators included frequency of “sufficiently active during leisure time,” “inactive in four domains of physical activity (leisure, work, transportation, and housework),” and “habit of watching television for long periods.” Reliability was assessed by comparing results of the original telephone interview with those of another identical interview repeated after seven to 15 days. Validity was assessed by comparing the results of the telephone interview with those of three 24-hour recalls (reference method) carried out in the week following the original interview. RESULTS: Frequencies obtained for of the three evaluated indicators were either identical or very similar for the first and second telephone interviews. Kappa coefficients ranged from 0.53 to 0.80, indicating good reliability for all indicators. In relation to the reference method, all indicators showed 80% or higher specificity, and sensitivity values were 69.7% for “watching television for long periods,” 59.1% for “inactive in four domains,” and 50% for “sufficiently active during leisure.” CONCLUSIONS: The indicators of physical activity and sedentariness included in the system seem reliable and sufficiently accurate. If kept operational in coming years, this system may provide Brazil with a useful instrument for evaluating public policies aimed at promoting physical activity and controlling non-transmissible chronic diseases associated with sedentariness.